2014
DOI: 10.1016/s1473-3099(13)70268-8
|View full text |Cite
|
Sign up to set email alerts
|

Single dose primaquine for clearance of Plasmodium falciparum gametocytes in children with uncomplicated malaria in Uganda: a randomised, controlled, double-blind, dose-ranging trial

Abstract: Wellcome Trust and the Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
135
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 37 publications
7
135
2
Order By: Relevance
“…There were no betweengroup differences in initial asexual parasite clearance in the main trial (29), so this phenomenon is unlikely to have been influential in the present substudy. In addition, and in support of the validity of our findings, the gametocyte carriage times in the two groups (13 and 20 days in the artemether-lumefantrine and artemisininnaphthoquine groups, respectively) are in accord with those in studies that have used the same mathematical model (12.8 days after artemether-lumefantrine in Ugandan children ages 1 to 10 years [39], 13.4 days after treatment with sulfadoxine-pyrimethamine plus artesunate [SP-AS] in Kenyan children ages 0.5 to 10 years [4], and 28 days in a young Tanzanian cohort also treated with SP-AS [4]). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There were no betweengroup differences in initial asexual parasite clearance in the main trial (29), so this phenomenon is unlikely to have been influential in the present substudy. In addition, and in support of the validity of our findings, the gametocyte carriage times in the two groups (13 and 20 days in the artemether-lumefantrine and artemisininnaphthoquine groups, respectively) are in accord with those in studies that have used the same mathematical model (12.8 days after artemether-lumefantrine in Ugandan children ages 1 to 10 years [39], 13.4 days after treatment with sulfadoxine-pyrimethamine plus artesunate [SP-AS] in Kenyan children ages 0.5 to 10 years [4], and 28 days in a young Tanzanian cohort also treated with SP-AS [4]). …”
Section: Discussionsupporting
confidence: 88%
“…In areas with a high entomological inoculation rate, artemether-lumefantrine may reduce the likelihood of posttreatment transmission (40), albeit at the cost of late recurrences of asexual forms, especially P. vivax where this species is transmitted (29). Single-dose primaquine kills P. falciparum gametocytes and has been proposed as an addition to P. falciparum treatment to reduce transmission (39). However, given its potential hemolytic toxicity and questions regarding the most suitable socioeconomic and epidemiologic settings for it use, it is currently not a part of currently recommended therapy for P. falciparum infection (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…At the time malaria patients seek medication, there would already be late stage IV and V gametocytes circulating in their system (Eziefula et al, 2014). Late stage gametocytes particularly make a scientifically credible stage to block transmission as they are the only form of P. falciparum capable of infecting a female Anopheles mosquito (Sinden et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Later in the same year, the WHO Malaria Advisory Committee modified their recommendation to a single 0.25-mg/kg PQ dose to alleviate concerns of serious toxicity in patients with glucose-6-phosphate dehydrogenase deficiency and in consideration of the benefits of disseminating PQ as a transmission blocking drug to a high proportion of patients within a population. In vivo studies conducted in Southeast Asia and Africa showed that PQ added to ACTs for treating P. falciparum malaria exhibited effective gametocyte clearance in patients (6)(7)(8)(9). Even when added to non-artemisinin-based regimens, PQ (Ͼ0.4 mg/kg) was able to drastically reduce the proportions of people with detectable gametocytemia (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%